2004
DOI: 10.1002/ijc.20527
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of tissue factor by RNA interference in human melanoma LOX‐L cells reduces pulmonary metastasis in nude mice

Abstract: Tissue factor (TF), a transmembrane protein, initiates the blood coagulation cascade by complexing with its serine protease ligand factor VII(a) (FVIIa), ultimately leading to thrombin generation, fibrin deposition and platelet aggregation. TF is aberrantly expressed in many solid tumors and tumor cell lines 1-4 with higher expression levels in malignant tumor cells compared to their nonmalignant counterpart. Subsequent results suggested that TF participates in the tumor growth and dissemination of various can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 64 publications
(76 reference statements)
1
29
0
Order By: Relevance
“…The moderate effects on localized growth are consistent with in vitro proliferation experiments (Fig. 1D), and our previous data with human cells exhibiting stable tissue factor knockdown indicated a very marginal effect of tissue factor knockdown on proliferation compared with the effects on colony formation and in vivo metastasis (18).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The moderate effects on localized growth are consistent with in vitro proliferation experiments (Fig. 1D), and our previous data with human cells exhibiting stable tissue factor knockdown indicated a very marginal effect of tissue factor knockdown on proliferation compared with the effects on colony formation and in vivo metastasis (18).…”
Section: Discussionsupporting
confidence: 89%
“…Formation of a complex between tissue factor and activated FVII (FVIIa) triggers a substantial activation of cell signaling, leading to up-regulation of the expression of >25 immediate early genes (26). Analysis of the global effects on gene expression of a human melanoma cell line exhibiting stable depletion of tissue factor expression through short hairpin RNA -mediated RNA interference (27) identified 44 and 228 genes that were up-regulated and down-regulated, respectively (18). Genes involved in cell growth, invasion, and angiogenesis were down-regulated in tissue factor -deficient cells, whereas up-regulated genes included those with known functions in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…TF downregulation by shRNA induces upregulation of vimentin, a marker of mesenchymal differentiation Wang et al 95 MSCs indicates mesenchymal stem cells; HSCs, hemopoietic stem cells; PAR-1/2, protease-activated receptor 1/2; NSCs, neural stem cells: ESCs, embryonic stem cells; TF, tissue factor. plified by several findings: First, we found that not all tumorigenic cells with properties of CSCs/TICs express TF on their surfaces.…”
Section: Vimentinmentioning
confidence: 99%
“…These target molecules include growth factors and receptors, anti-apoptotic proteins, as well as downstream signal transduction proteins, all crucial to tumor cell growth and survival. [39][40][41][42][43][44] In contrast, siRNA-hVDAC1 is expected to inhibit the development of a cancer tumor by suppressing VDAC1 expression. Thus, targeting hVDAC1 expression holds great promise for the field of cancer therapy.…”
Section: Discussionmentioning
confidence: 99%